2020
DOI: 10.1007/s12011-020-02313-6
|View full text |Cite|
|
Sign up to set email alerts
|

High-Dose Aluminum Exposure Further Alerts Immune Phenotype in Aplastic Anemia Patients

Abstract: This study explored the relationship between immunological status and clinical characteristics of aplastic anemia (AA) patients to plasma aluminum levels, which were increased after constant exposure to high levels of this metal. Sixty-two AA patients (33 cases with high and 29 cases with low or no exposure to aluminum) and 30 healthy controls were selected for this study. Aluminum in human albumin solution was measured by inductivity coupled plasma mass spectrometry. IL-10, IL-12, IL-17, and INF-γ levels were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Even though Al is not required for any biological process in humans and animals, it can be a metallic toxicant at high concentrations after natural or unnatural exposure [ 4 , 5 ]. Exposure to Al has been linked to several adverse health effects, such as asthma [ 6 , 7 ], bone disease [ 8 , 9 , 10 ], immunotoxicity [ 11 , 12 ], congenital malformations [ 13 ], and reproductive toxicity in laboratory animals [ 14 , 15 ]. For example, children with early life exposure to a high level of Al had lower lumbar spine bone mass and lower hip bone mass [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Even though Al is not required for any biological process in humans and animals, it can be a metallic toxicant at high concentrations after natural or unnatural exposure [ 4 , 5 ]. Exposure to Al has been linked to several adverse health effects, such as asthma [ 6 , 7 ], bone disease [ 8 , 9 , 10 ], immunotoxicity [ 11 , 12 ], congenital malformations [ 13 ], and reproductive toxicity in laboratory animals [ 14 , 15 ]. For example, children with early life exposure to a high level of Al had lower lumbar spine bone mass and lower hip bone mass [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, aluminum has been associated with many health problems, especially respiratory diseases, malignancies such as bladder, lymphatic, and hematologic cancers, and conditions such as aplastic anemia. 11 , 12 In a recent study conducted in a human colorectal cancer cell line, aluminum was shown to have wide-ranging effects on cells, such as promoting migration and invasion and suppressing adhesion. Exposure to aluminum also altered the expression and secretion of various proteins associated with angiogenesis, tumorigenesis, and metastasis, including E-cadherin, vimentin, Snail, transforming growth factor-β, matrix metalloproteinases 7 and 9, and vascular endothelial growth factor.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning humoral immunity, Al exposure could affect immunoglobins and complement levels in human and animal models. In a recent study, high Al exposure was associated with significant depletion of complement components among the studied anemic patients (Zuo et al, 2021). As for IgM and IgG levels, Synzynys et al (2004) showed that their levels dramatically reduced after consuming a dosage of aluminum chloride (0.04 M), resulting in a severe immunosuppressive impact in mice.…”
Section: Both Cytokines;mentioning
confidence: 96%
“…Inhalation and ingestion of metal fumes and dust, respectively, are considered the main routes of exposure where these metals get accumulated in the body. Although the impact of heavy metals on the immune system among human populations is poorly understood, however, several recent studies illustrated the immunological impact of human exposure to Aluminum (Al) and Lead (Pb) generously (Fenga et al, 2017;Pukanha et al, 2020 andZuo et al, 2021).…”
Section: Introductionmentioning
confidence: 99%